2018
DOI: 10.1002/acr.23418
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Impact of Decisions to Adjust Disease‐Modifying Antirheumatic Drug Therapy for Rheumatoid Arthritis Patients With Active Disease

Abstract: Adjusting DMARDs within 90 days was associated with shorter times to LDAS, but many patients with persistent MHDAS waited >90 days to adjust DMARDs. Interventions are needed to address the timeliness of DMARD adjustments for RA patients with MHDAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…19 Staff shortages were perceived to impact negatively on timing of treatment for patients with EIA, which in turn impacts on clinical outcomes. 20 In relation to the breadth and expertise of MDT members, although having autonomous nurses was part of the criteria for ‘treat to target’ quality indicators (and therefore not a surprise that this was a feature of higher quality units), this study explains how this was related to quality, predominantly through sharing responsibility for holistic care and having more team members available to provide care. The benefits of non-medical prescribing to patient experience and outcomes have been reported widely, 21 22 with such roles being key to providing patient education, 23 ensuring patients receive holistic support 24 ; and providing more responsive prescribing.…”
Section: Discussionmentioning
confidence: 93%
“…19 Staff shortages were perceived to impact negatively on timing of treatment for patients with EIA, which in turn impacts on clinical outcomes. 20 In relation to the breadth and expertise of MDT members, although having autonomous nurses was part of the criteria for ‘treat to target’ quality indicators (and therefore not a surprise that this was a feature of higher quality units), this study explains how this was related to quality, predominantly through sharing responsibility for holistic care and having more team members available to provide care. The benefits of non-medical prescribing to patient experience and outcomes have been reported widely, 21 22 with such roles being key to providing patient education, 23 ensuring patients receive holistic support 24 ; and providing more responsive prescribing.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, a recent study that explicitly modeled the relationship between MTC and low disease activity status found that adjustments within 90 days of active RA resulted in shorter times to low disease activity status (6).…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to adjust for previous MTC, stability of disease activity, and DMARDs dispensed in the previous month but did not explicitly model the time‐varying treatment process. Nevertheless, a recent study that explicitly modeled the relationship between MTC and low disease activity status found that adjustments within 90 days of active RA resulted in shorter times to low disease activity status (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RACER encompasses a registry of longitudinal data collected from a cohort of over 1000 patients with RA visiting the University of Pittsburgh Rheumatoid Arthritis center. 19 Control participants (n = 101) were volunteers recruited from (1) participants of the Heart Strategies Concentrating on Risk Evaluation (SCORE) study (n = 28) and ( 2) the general population by flyers/advertisements (n = 73). Heart SCORE is a longitudinal, descriptive community-based research study of 2000 white and black participants in southwestern Pennsylvania.…”
Section: Study Populationmentioning
confidence: 99%